An underwater superoleophobic nanofibrous cellulosic membrane for oil/water separation with high separation flux and high chemical stability. Issue 6 (29th January 2018) - Hong, Seong Kyung; Bae, Seonghan; Jeon, Hyungkook; Kim, Minseo; Cho, Seong J.; Lim, Geunbae
Abstract : A nanofibrous cellulosic membrane effectively separates large amounts of oil/water mixtures in chemically harsh environments at high fluxes. Abstract : Oil spills and an increasing demand for the treatment of industrial oily wastewater are driving the need for continuous large-scale oil/water separation processes. Herein, we report a nanofibrous cellulosic membrane (NFC membrane) for the continuous high-flux separation of large amounts of oil/water mixtures. The NFC membrane was fabricated using wet electrospinning, a facile yet effective method for stacking nanofibrous membranes with uniform porous structures on a substrate. Owing to its cellulosic nature, the membrane showed excellent underwater superoleophobicity along with robust chemical stability and was able to separate oil/water mixtures at efficiencies exceeding 99%. Repetitive oil/water separations could be performed using a single membrane, during which the oil content in the filtrate remained extremely low (<29 ppm). The nanofibrous membrane exhibited a fine porous structure that was interconnected throughout the membrane, resulting in a high oil intrusion pressure (>30 kPa) that allowed not only gravity-driven but also pressure-driven separation of oil/water mixtures. The separation flux reached 120 000 L m −2 h −1 during pressure-driven separations, which is a very promising feature for actual applications such as the large-scale treatment of industrial oily wastewater.